Before-after evaluation of patient length of stay in a rehabilitation context following implementation of an electronic patient journey board. (February 2020) - Rolls, David; Khanna, Sankalp; Lloyd, Nicola; Reeson, Andrew; Jayasena, Rajiv; McCormick, Christopher; Hakkennes, Sharon
Highlights: Benefits from using an electronic patient journey board system. Change to electronic system associated with shorter inpatient rehabilitation episodes. Estimated reduction of four days in case—mix adjusted lengths of stay. Estimated reduction of 18 % in episode cost from shorter durations. Abstract: Purpose: To investigate whether the installation of electronic patient journey boards in an inpatient adult rehabilitation centre in Victoria, Australia, is associated with shorter lengths of stay for admitted adult rehabilitation patients. Methods: A retrospective before-after analysis of 3 259 adult inpatient rehabilitation episodes from 2013 to 2018 was performed, analysing case-mix adjusted lengths of stay. Results: A reduction in case-mix adjusted length of stay of 4.1 days per episode (95 % confidence interval: 2.0–6.4 days) was found. The corresponding reduction in hospital costs was estimated to be $3 738 per episode (95 % confidence interval $2 398–$4 983). Conclusions: Installation of electronic patient journey boards was associated with shorter lengths of stay in an inpatient adult rehabilitation centre. Additional research is needed to 1) provide further evidence of the causal effect of the boards on length of stay, and 2) investigate the mechanisms by which they reduce lengths of stay (e.g., increased currency of information, changes to procedures, remote viewing) in rehabilitation settings.